THE USE OF COMIC STRIPS TO IMPROVE STUDENTS’ READING COMPREHENSION - Nispa; Muhammad Ihsan; Mohammad Syafri (Datokarama English Education Journal, 2023)
This study aims to find the effectiveness the use of comic strips in class VIII SMPN 13 Palu. Pre-experimental design that required pre-test and post-test groups, used in this research. The population in this study were 191 eighth-grade students of SMPN 13 Palu. The sample of this study was 15 students. selected using  quota sampling technique. The data had been collected were analyzed quantitavely. The results of data analysis showed that the average score of students in the pre-test (31.67), and the post-test scores of students increased after being given treatment used comic strip media with an average value 79.67. Ttable significance level for alpha ɑ 0.05 or 5% degrees of freedom (df 28 = 1.701). The Tobserve value higher than Ttable, namely 10.921 > 1.701, then the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It can be proven that there is a significant improvment between the results of used comic strips in taught reading comprehension of narrative texts to second-grade students of SMPN 13 Palu. The implication of this research was the use of comic strips as a media can improve students' reading comprehension at SMPN 13 Palu. It is hoped that prospective educators can present teaching materials well and interestingly so that they are easy to understand, joyful, and can make a comfortable learnned atmosphere, so that the class becomes more conductive.